2021
DOI: 10.3389/fmed.2021.685999
|View full text |Cite
|
Sign up to set email alerts
|

The Auxiliary Diagnostic Value of a Novel Wearable Electrocardiogram-Recording System for Arrhythmia Detection: Diagnostic Trial

Abstract: Background: AMAZFIT®, a novel wearable electrocardiogram (ECG)-recording system is used for the measurement, acquisition, and storage of single-lead cardiac waveforms for adults. The aim of the study was to evaluate the accuracy of AMAZFIT® for diagnosing arrhythmia in older patients.Methods: From May to December 2019, we recruited 291 elderly individuals with an average age of 78±10 years old, and 41.9% women. All cardiac waveforms were obtained from the AMAZFIT® which included limb and chest leads. Two train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Of the 36 articles, 24 (66%) evaluated the devices’ capabilities to diagnose rhythm disorders [ 15 - 17 , 21 , 24 , 25 , 29 - 35 ,​ 37 - 43 , 49 - 56 ], whereas 7 (20%) reported on capabilities to detect rhythm disorders and other heart conditions, such as cardiomyopathy, conduction disorders, and cardiac ischemia [ 18 , 22 , 23 , 28 , 36 , 45 , 57 ]. Finally, for 3 (14%) of the 22 devices, the evidence found was regarding the evaluation of the quality of the signals recorded by them [ 14 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 36 articles, 24 (66%) evaluated the devices’ capabilities to diagnose rhythm disorders [ 15 - 17 , 21 , 24 , 25 , 29 - 35 ,​ 37 - 43 , 49 - 56 ], whereas 7 (20%) reported on capabilities to detect rhythm disorders and other heart conditions, such as cardiomyopathy, conduction disorders, and cardiac ischemia [ 18 , 22 , 23 , 28 , 36 , 45 , 57 ]. Finally, for 3 (14%) of the 22 devices, the evidence found was regarding the evaluation of the quality of the signals recorded by them [ 14 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Apple Watch, KardiaMobile (AliveCor), Bittium Faros 180 (Bittium), and Move ECG studies reported specificities of <90% (range 81%-86%) for AF detection [ 15 , 33 , 43 ]. For other rhythm disorders, the studies reported specificities of >85% (range 85.9%-99,6%), whereas the sensitivities ranged from 25% to 96% [ 18 , 22 , 45 ]. For cardiac ischemia detection, the Apple Watch and Beurer ME 80 (Beurer GmbH) were evaluated, and the studies reported specificities of >90% (range 93%-100%) and sensitivities of <65% (range 7%-64%); these studies included 40 and 13 participants, respectively [ 23 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lubitz et al [ 24 ], Zhang et al [ 25 ], Perez et al [ 26 ], Jacobsen [ 27 ], Heo et al [ 28 ], Reverberi et al [ 29 ], Haverkamp [ 30 ] and Dörr et al [ 31 ] conducted prospective clinical trials. Wang et al [ 32 ], Proesmans et al [ 33 ], Himmelreich et al [ 34 ], William et al [ 35 ], Tison et al [ 36 ], and McManus et al [ 37 ] conducted retrospective cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies were conducted in hospital settings. Twelve of the studies conducted in inpatient settings were among high-risk participants who were admitted for screening of AF and other cardiology-related diagnoses in cardiac and other wards [ 25 , 27 , 30 , 38 , 43 , 46 , 47 ], cardioversion procedures [ 29 , 37 , 40 , 41 ], and initiation of anti-arrhythmic drugs [ 35 ]. Eight studies were conducted in outpatient settings with data obtained from patients who were visiting clinics [ 31 , 33 , 34 , 36 , 44 , 45 , 48 •, 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation